Analisis Penerapan Media Pembelajaran Inovatif IPA Di SD - Erina Putri, Syifa Azzahra; Rahma, Nurfajrina Mawaddah; Zulfa, Indana (SM Institute, 2023)
The purpose of this study was to explain the application of learning media and the impact of the application of innovative learning media in science lessons in grade VI SD. This type of research is descriptive qualitative. Data collection techniques used interviews, observation, and documentation. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions. The research subjects or data sources were class teachers and students of grade VI of SD Negeri 10 Kalideres. The results showed that the application of innovative learning media called Borama had a good impact. The conclusion of this study shows that the application of innovative learning media in science subjects, students become more understanding, not bored in learning activities and improve learning outcomes.